2011
DOI: 10.1590/s0103-50532011000100022
|View full text |Cite
|
Sign up to set email alerts
|

NMR study of 1,4-dihydropyridine derivatives endowed with long alkyl and functionalized chains

Abstract: Neste trabalho, realizou-se um estudo por ressonância magnética nuclear de 1 H, 13 C e 15 N de derivados de 1,4-dihidropiridinas que contêm, nos grupos ésteres das posições C-3 e C-5, longas cadeias alquílicas ou funcionalizadas. Atribuíram-se inequivocamente os sinais dos espectros utilizando experimentos 1D e 2D (DEPT, nOe, HMQC, HMBC, COSY). The 1 H , 13 C and 15 N NMR spectroscopic data for 1,4-dihydropyridine endowed with long alkyl and functionalized chain on C-3 and C-5, have been fully assigned by comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…These findings have been accounted for by the strong push–pull effect of the groups linked to the olefinic double bonds like ones previously observed in other related systems. The carbon signal of C 4 is in agreement with the previous data [ 32 , 33 ] and appears at 28.5 ppm for the aliphatic R and in the interval 34.2–39.8 ppm when R is aromatics.…”
Section: Resultssupporting
confidence: 92%
“…These findings have been accounted for by the strong push–pull effect of the groups linked to the olefinic double bonds like ones previously observed in other related systems. The carbon signal of C 4 is in agreement with the previous data [ 32 , 33 ] and appears at 28.5 ppm for the aliphatic R and in the interval 34.2–39.8 ppm when R is aromatics.…”
Section: Resultssupporting
confidence: 92%
“…In the downfield region, between 6 and 8.5 ppm, several signals can be assigned to the presence of rings of pyrrole (6.5 and 7 ppm) and 1,4‐dihydropyridine. In particular, the resonance structures of the dihydropyridine allow us to account for the presence of a chemical shift at around 8.4 ppm . The 1 H‐NMR spectrum of the membrane does not show specific changes compared to the spectrum of PK‐PDAP.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the former is unlikely, as unsubstituted dihydropyridines are very unstable. [39,40] However, in some publications, [41,42] dihydropyridines were detected upon pyridine reduction with lithium aluminum hydride or zinc hydride. These studies demonstrated that isomeric dihydropyridines can give rise to NMR signals at 22-25, 28-30, 40-50, and 90-100 ppm.…”
Section: Pyridine Complexesmentioning
confidence: 99%